2022
DOI: 10.3390/polym14040769
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization and Antibacterial Applications of Cellulose-Based Composite Hydrogels

Abstract: Pathogens, especially drug-resistant pathogens caused by the abuse of antibiotics, have become a major threat to human health and public health safety. The exploitation and application of new antibacterial agents is extremely urgent. As a natural biopolymer, cellulose has recently attracted much attention due to its excellent hydrophilicity, economy, biocompatibility, and biodegradability. In particular, the preparation of cellulose-based hydrogels with excellent structure and properties from cellulose and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 187 publications
1
14
0
Order By: Relevance
“…Our results also showed that cellulosic materials with excellent physical and biological properties are favorable candidates for biomedical products, due to their low cytotoxicity, biodegradability, and biocompatibility …”
Section: Resultssupporting
confidence: 62%
“…Our results also showed that cellulosic materials with excellent physical and biological properties are favorable candidates for biomedical products, due to their low cytotoxicity, biodegradability, and biocompatibility …”
Section: Resultssupporting
confidence: 62%
“…Cellulose-based hydrogels are a promising adsorbent biomaterial and present several advantages compared to other conventional synthetic adsorbents, due to their low cost and high abundance, considerable biocompatibility, biodegradability, nontoxicity, good thermal/chemical stability and excellent adsorption capacity. However, the main inconvenience of cellulose is that it cannot be used in its natural form like other biopolymers due to the abundance of hydroxyl groups; however, thanks to those groups, as well as other hydrophilic functional groups, namely carboxyl and aldehyde groups, it can be functionalized through several chemical reactions to form cellulose-based hydrogels [ 118 , 119 , 120 ]. Hu et al (2022) developed an aminocelullose-dialdehyde xylan composite hydrogel with silver (Ag), synthesized via green method by Schiff-base reaction cross-linking, followed by an immersion step in silver nitrate solution, which exhibited excellent antibacterial properties against E. coli and promising wound healing performance [ 121 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of antimicrobial action of AgNPs is not yet fully understood, but various studies have shown that many different biochemical pathways can be affected, leading to cellular death. There are four possible mechanisms by which AgNPs exhibit antimicrobial activity: cell membrane destruction, formation of reactive oxygen species by silver catalysis, inhibition of ATP production, and inhibition of DNA replication upon silver penetration into the cell. The mechanisms of activity can be discussed in the context of both microbiology and biochemistry.…”
Section: Introductionmentioning
confidence: 99%